Do firms with works councils prefer agreeable job applicants? : A discrete choice experiment - Pfeifer, Harald [Verfasser]; Wehner, Caroline [Verfasser]; De Grip, Andries [Verfasser]; Kensbock, Julia M. [Verfasser] (My University, 2025)
"Works councils in many countries are involved in dismissal procedures and may therefore invoke high hold-up costs for firms laying off workers. To avoid these conflicts, firms with a works council may have a stronger preference for more agreeable job applicants who have a low risk of dismissal. We conduct a discrete choice experiment among recruiters to assess their preferences regarding job applicants' personality traits and competence. In line with our expectations, we find that recruiters from works-council firms more strongly prefer agreeable job applicants. We also find that more agreeable recruiters choose more agreeable employees, indicating a similarity-attraction effect." (Authors‘ abstract; BIBB-Doku)
Keywords: S 5.3 Personalentwicklung; S 5.3 Personalentwicklung S 3.5.4 Sozialpartner; 370; Personalabteilung; Führungskraft; Personaleinstellung; Personalauswahl; Persönlichkeitsmerkmal; Betriebsrat; Einflussfaktor